Linguistic Landscape Labelling on Business Signboards in Medan, Indonesia and in Bangi, Malaysia - Nurmala, Dewi; Dewi, Ratna Sari; binti Hisham, Hadirah Amalin; Wardana, Muhammad Kiki; Daniel, Muhammad (Westscience Press, 2025)
This article is the result of the community service activity of a team of lecturers and students of Universitas Muslim Nusantara Al-Washliyah from the English literature study program. The purpose of this community service is to share knowledge of linguistic landscape labelling of business signboards. Landscape linguistics is a study of language use in public spaces. Signs on business signboards use some languages based on the regulation of the city or country. Medan and Bangi are two cities that have different rules of using language on business signboards. The location of community service at Universiti Kebangsaan Malaysia, Selangor, Malaysia. This activity was carried out using the extension method and socialization of the linguistic landscape labelling on business signboards. The benefit of this activity is to add the knowledge of the participant about linguistic landscape labelling on business signboards. The stages of activities carried out are location surveys, licensing arrangements, material preparation and community service training. Through this activity, it is hoped that it will increase the knowledge and insight of the participant.